SITUATION AND COMPETENCY OF FIRST RESPONDER IN PREPAREDNESS ON FACING EMERGENCY TO IMPROVE PUBLIC SAFETY IN THE UNIVERSITY - Suci Tuty Putri; Sehabudin Salasa; Sri Sumartini (Nurse and Health: Jurnal Keperawatan, 2020)
Background: Cardiovascular disease and trauma caused by accidents remain the leading cause of death. Data by WHO reveals that 17,9 million people die from cardiovascular disease before reaching hospital. The problem is caused by the first aid mistake; hence, a prompt and effective response action of the first responder is important to handle out-of-hospital emergency care. The need for care and human resources is the biggest and most important component to act as the first responders.Objectives: The research aims to discover evaluation emergency situation in university and the competency level of the first responder taking first aid training in affect the way patients are managed during an emergency.Methods: The method employed is mixed methods consists of FGD with a four-stage contingency planning approach and quasi-experimental design of one group post-test that was conducted to obtain quantitative data. There were 30 participants in this research. Thematic and descriptive analysis tests were used to analyze the dataResults: The results show that there are four important things in developing an emergency system in the university area which are a distribution of operational area, communication system, Developing emergency system, and sustainable improvement of first responder capacity. The results of the competency assessment show that the average knowledge level of the participants is 79.5, and their psychomotor level is above 80%.Conclusion: First aid training is important to given for first responder to improve safety in the university. Keywords: Public Safety Center, First Responder, Emergency.